Change in patient nutritional knowledge following coronary artery bypass graft surgery - L. van Rooy; Yoga Coopoo (AOSIS, 2017)
Introduction: In order to reduce coronary artery disease (CAD) risk, moderate physical activity should be combined with other lifestyle modifications, such as proper nutrition, to have a dramatic impact. This necessitates educational and preventative measures, which should begin in childhood and continue throughout life. Aim: The aim of this study was to measure the change in nutrition knowledge of coronary artery bypass graft patients by implementation of a lifestyle intervention programme. Methods: The Hawkes andNowak Nutrition Knowledge Questionnaire (1998) was administered to 18 coronary artery bypass graft (CABG) patients to assess the change in nutrition knowledge. Results: Significant improvements were noted in the nutrition knowledge score (18.9 ± 3.4-23.2 ± 4.5; p = 0.000). Although all components measured exhibited improvements in knowledge, cholesterol reduction knowledge (5.3 ± 1.8-7.2 ± 1.8; p = 0.0066), low fat food knowledge (3.8 ± 2.3-5.1 ± 2.7; p = 0.011) and high fibre food knowledge (4.1 ± 1.4-4.7 ± 1.1;p = 0.022) exhibited the highest and most significant improvements. Conclusion: Notably, these significant improvements in nutrition knowledge points toward effective education being delivered during the intervention. Cardiac rehabilitation has proved to be effective in changing lifestyle habits in a holistic way and this study further shows an improvement in nutritional knowledge based on sound educational principles.